The Influence of Financial Performance and Independen Commisionaners on Company Value - Astuti, Wati Aris; Andayani, Endro; Dewi, Novita Sinta (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study aims to determine the effect of financial performance and independent commissioners on firm value. The methods used in this research are descriptive and verificative methods with a quantitative approach. The population in this study consists of financial statements of infrastructure companies listed on the Indonesia Stock Exchange from 2019 to 2023. The sampling technique used in this study is purposive sampling. The data analysis method employed is multiple regression analysis using the Statistical Product and Service Solutions (SPSS) software version 22. The results of this study indicate that financial performance has a positive effect on firm value, while independent commissioners do not have an effect on firm value.